MODES OF INDEPENDENT MIGRATION OF INDONESIAN MIGRANT WORKERS IN ENTERING AND WORKING IN MALAYSIA THROUGH NON-PROCEDURAL CHANNELS - Lisbet Corry; Adi Nur Rohman (RADJA PUBLIKA, 2025)
This study examines the modes of independent migration of Indonesian Migrant Workers (PMI) in entering and working in Malaysia through non-procedural pathways. The phenomenon of non-procedural migration has become a significant concern as it increases the risk of rights violations, creates uncertainty in working conditions, and poses challenges for the government in monitoring and protecting migrant workers. This study aims to analyze the modes of independent migration undertaken by PMI, the factors driving non-procedural migration, and its implications for working conditions and legal protection in Malaysia.This research employs a qualitative approach using a case study method, involving in-depth interviews with migrant workers, migration observers, and government representatives, as well as analysis of relevant documents. The findings indicate that independent migration modes involve informal routes and intermediary networks that play a role in job placement, while the driving factors include socio-economic pressures, limited access to official migration mechanisms, and perceptions of bureaucratic delays.The implications of non-procedural migration include wage uncertainty, unsafe working conditions, minimal legal protection, and heightened vulnerability to exploitation and rights violations. The study also finds that the government faces difficulties in monitoring non-procedural migrant workers due to the lack of data, weak cross-sectoral coordination, and the dominance of informal networks. Based on these findings, the study recommends strengthening official migration procedures, increasing outreach and education for prospective migrant workers, enhancing legal protection for PMI in Malaysia, as well as promoting cross-border collaboration and community-based assistance. This study contributes to a deeper understanding of the complexity of independent non-procedural migration and risk mitigation strategies for migrant workers, thereby helping to better protect the rights, safety, and welfare of migrant workers.